Institutionalisation, deinstitutionalisation and change: The context of policy change for software exports in Costa Rica - Brian Nicholson; Sundeep Sahay (The University of Manchester, Manchester Business School, 2008)
This paper addresses deinstitutionalisation from a longitudinal perspective. Drawing on the case of software exports policymaking in Costa Rica, it analyses persistence and change paying particular attention to formation of dissensus, understood as lack of unanimity on the value of an activity that is sufficient to destabilise institutional norms and activities. The role of cultural and political factors in deinstitutionalisation or persistence is considered. Based on the empirical data, a framework for understanding political and cultural dynamics in deinstitutionalisation is proposed.
Keywords: 330; Institutionalismus; Institutioneller Wandel; Außenwirtschaftspolitik; Softwareindustrie; Costa Rica